Hubungan Self Care dengan Kualitas Hidup Pasien TB Paru di Rumah Sakit Efarina Etaham Berastagi Tahun 2025 - Mindo Rahel Simatupang; Romauli Pakpahan; Danuarta Azaria Abednego; Nike Naibaho (Jurnal Minfo Polgan, 2025)
Tuberculosis (TB) is a chronic infectious disease that not only impacts physical health but also affects the overall quality of life of sufferers. Good self-care practices are believed to improve the quality of life of pulmonary TB patients, particularly in the physical, psychological, social, and spiritual aspects. This study aims to determine the relationship between self-care and the quality of life of pulmonary TB patients at Efarina Etaham Hospital in Berastagi. This study used a correlational analytical design with a cross-sectional approach. A sample of 76 respondents was selected using proportional random sampling. The research instrument consisted of a self-care and quality of life questionnaire. Data analysis was performed using univariate and bivariate methods using the Spearman Rank test. The results showed that the majority of respondents had good self-care (51.3%) and a fair quality of life (68.4%). The Spearman Rank test showed a positive and significant relationship between self-care and quality of life, with a p-value of 0.000 and a correlation coefficient of r = 0.680. This means that the higher the self-care behavior of patients, the better their perceived quality of life. This study concludes that good self-care significantly contributes to improving the quality of life of pulmonary TB patients, and therefore needs to be encouraged through ongoing education and support from healthcare professionals and the surrounding community.